'Hidden identities': perceptions of sexual identity in Beijing. (8th July 2017) - Miles‐Johnson, Toby; Wang, Yurong
Abstract: This article draws upon responses given by volunteers who work in the Beijing LGBT Centre regarding perceptions of sexual identity, and how Chinese culture affects hidden or open sexual identities of Chinese lesbian and gay people in this region. The insights gained from those working carefully to create social change offers an important and original contribution to the field of gay and lesbian studies in China. The findings indicate the volunteers at the Beijing LGBT Centre are frustrated by the lack of acceptance of non‐heterosexual relationships among Chinese culture and society, and by the disregard of lesbian gay and bisexual (LGB) people by the Chinese government. The findings also illustrate stigmatization of homosexuality in China is enacted in structural terms (such as in the lack of policy, legislation and positive endorsement by governmental and socio‐political organizations), public expression (such as negative attitudes, beliefs or reactions towards LGB people) and internalized repression (through fear of stigmatization, and subsequent abuse due to negative societal attitudes and discrimination). Influenced by the Chinese tradition of conforming to group values, the findings from this study show that volunteers at the Beijing LGBT Centre believe LGB people in China are generally hesitant to disclose their sexual identities, and reject the idea that there had been a collective shift in Chinese culture regarding increased acceptance of LGB people. It also finds volunteers at the LGBT Centre in Beijing blame Chinese culture for its lack of acceptance of non‐heterosexual relationships, and state stigmatization of homosexuality in China is due to deep‐rooted cultural homophobia.